2019
DOI: 10.1161/strokeaha.118.023614
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Angiography Versus Digital Subtraction Angiography for Postclipping Aneurysm Obliteration Detection

Abstract: Background and Purpose— Digital subtraction angiography has been used as the gold standard to confirm successful aneurysmal obliteration after aneurysm clipping procedures using titanium or cobalt alloy clips. Computed tomographic angiography is a newer, less invasive imaging technique also used to confirm successful aneurysmal obliteration; however, its use compared with digital subtraction angiography remains controversial. Methods— A comprehensive li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Our results, measured using the noncontact-type X-ray analyzer, showed the effective X-ray energy at 120 kV as 55.9 keV and 48.8 keV in the UHR-CT and conventional CT used at our institute, respectively (unpublished data). A recent meta-analysis indicated that CTA was not as accurate as DSA in ruling out postclipping remnant aneurysms; [6] the reason is metal artifacts from titanium clips, which always matter in postoperative evaluations. [4] e current case report highlights that UHR-CTA is comparable with DSA in evaluating intracranial aneurysms even after the titanium clips were placed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results, measured using the noncontact-type X-ray analyzer, showed the effective X-ray energy at 120 kV as 55.9 keV and 48.8 keV in the UHR-CT and conventional CT used at our institute, respectively (unpublished data). A recent meta-analysis indicated that CTA was not as accurate as DSA in ruling out postclipping remnant aneurysms; [6] the reason is metal artifacts from titanium clips, which always matter in postoperative evaluations. [4] e current case report highlights that UHR-CTA is comparable with DSA in evaluating intracranial aneurysms even after the titanium clips were placed.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, aneurysmal clips induce metal artifacts in CTA, which hinder precise evaluations of aneurysms. [4,6] e ultra-high-resolution computed tomography (UHR-CT) system recently became available, and we recently reported usefulness of UHR-CT in the detection of the subcallosal artery. [5] UHR-CT theoretically reduces metal artifacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,29 CTA of clipped aneurysms has generally not been as accurate compared with conventional angiography, especially for small aneurysms, when multiple clips were used, on small parent vessels, or when the aneurysm was in the vicinity of bony structures. 12,[30][31][32] These same technical limitations may explain the trend toward lower agreement for clipped aneurysm subgroups assessed by CTA compared with coiled aneurysms assessed by MRA.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 When one judges the comparative success of therapy in clinical reports, it would seem that comparing CTA results of clipping with MRA results of coiling would be problematic, given the different diagnostic accuracies of the 2 modalities. 11,12 This problem is particularly relevant for clinical trials: We cannot require a catheter angiogram solely for the purposes of the study when safer, noninvasive tests clinically suffice for most patients. 13 The problem is compounded by the proliferation of grading scales, many of which are tailored to various devices and treatment modalities.…”
mentioning
confidence: 99%